Pengaruh Pemasaran Digital dan Electronic Word of Mouth Terhadap Keputusan Pembelian pada Onebillion_Store.id di Kota Bandung - Kartini Febriani; Yuyun Yuniarsih (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
This research is motivated by the increasing use of the internet both to find information, to communicate, and even to shop, people can do it online via the internet. As well as the emergence of a new phenomenon in shopping for branded products at affordable prices which are known as thrifting, this activity is popular with the public, especially among teenagers or young people. This of course makes Onebillion_store.id have to develop a strategy that can make consumers decide to shop on the platform. The purpose of this study was to determine the effect of digital marketing and electronic word of mouth on purchasing decisions at onebillion_store.id in the city of Bandung. The population in this study are all onebillion_store.id consumers who know and have shopped at onebillion_store.id. While the sample in this study amounted to 99 respondents. The research method in this study used a quantitative approach with verification methods. The research results show that partially there is an influence of digital marketing on purchase decisions on onebillion_store.id by 42.8%, whereas the influence of electronic word of mouth on purchase decisions on onebillion_store.id is greater at 50.0%. The research results also reveal that simultaneously there is a positive influence of digital marketing and electronic word of mouth together on purchase decisions on onebillion_store.id by 92.8%. Therefore, it can be concluded that digital marketing and electronic word of mouth have an influence on purchase decisions, with electronic word of mouth contributing the most significant influence compared to digital marketing.